2022
DOI: 10.3390/d14070506
|View full text |Cite
|
Sign up to set email alerts
|

Bioclimatic Envelopes for Two Bat Species from a Tropical Island: Insights on Current and Future Distribution from Ecological Niche Modeling

Abstract: Bats perform critical ecosystem functions, including the pollination, seed dispersal, and regulation of invertebrate populations. Yet, bat populations are declining worldwide primarily due to habitat loss and other anthropogenic stressors. Thus, studies on bat ecology, particularly on environmental determinants of bat occupancy, are paramount to their conservation. High mobility, nocturnal behavior, and roosting site selection of bats make conventional surveys challenging. Moreover, little is known about geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…On the other hand, seasonal precipitation had the greatest impact on the predicted habitat suitability of E. labiatus , next to the population index. This result is consistent with the findings that seasonal precipitation has a significant impact on the distribution and suitability of bats (Bandara et al, 2022 ; Bilgin & Rebelo, 2012 ). In addition, it impacts the foraging and social structures of bats, potentially delaying reproduction and increasing the risk of their survival (Adams, 2010 ; Frick et al, 2010 ; Luo et al, 2020 ; Mello et al, 2009 ; Richter & Cumming, 2008 ; Sherwin et al, 2012 ; Weinberg et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, seasonal precipitation had the greatest impact on the predicted habitat suitability of E. labiatus , next to the population index. This result is consistent with the findings that seasonal precipitation has a significant impact on the distribution and suitability of bats (Bandara et al, 2022 ; Bilgin & Rebelo, 2012 ). In addition, it impacts the foraging and social structures of bats, potentially delaying reproduction and increasing the risk of their survival (Adams, 2010 ; Frick et al, 2010 ; Luo et al, 2020 ; Mello et al, 2009 ; Richter & Cumming, 2008 ; Sherwin et al, 2012 ; Weinberg et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Studies across the world have reported negative impacts both globally (Bellard et al, 2013) and regionally (Rebelo et al, 2010, in Europe;Hughes et al, 2012, in Southeast Asia;Thapa et al, 2021, in Nepal). Bandara et al (2022) found no or limited effects for Kerivoula picta and K. malpasi in Sri Lanka. Positive effects have also been observed in the Amazon (Costa et al, 2018), North America (Hayes & Piaggio, 2018) and Nepal (Thapa et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…Bandara et al. ( 2022 ) found no or limited effects for Kerivoula picta and K. malpasi in Sri Lanka. Positive effects have also been observed in the Amazon (Costa et al., 2018 ), North America (Hayes & Piaggio, 2018 ) and Nepal (Thapa et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…SDM and HSM involves the selection of appropriate environmental variables (Scherrer & Guisan, 2019 ). Traditionally, climate variables, such as bioclimatic data, have been widely employed for SDM and HSM (e.g., Amini Tehrani et al., 2020 ; Bandara et al., 2022 ; Bellamy et al., 2020 ; Cable et al., 2021 ; Luo et al., 2020 ; Raman et al., 2020 ; True et al., 2021 ; Wright et al., 2021 ). However, for the assessment of habitat suitability within the geographic range of a species (area of habitat (AOH); Brooks et al., 2019 ; Lumbierres et al., 2022 ), climate conditions are not necessarily decisive (Pearson et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%